2011
DOI: 10.1002/jcp.22570
|View full text |Cite
|
Sign up to set email alerts
|

Lipid raft localization of EGFR alters the response of cancer cells to the EGFR tyrosine kinase inhibitor gefitinib

Abstract: Epidermal growth factor receptor (EGFR) is overexpressed in many cancer types including ∼30% of breast cancers. Several small molecule tyrosine kinase inhibitors (TKIs) targeting EGFR have shown clinical efficacy in lung and colon cancers, but no benefit has been noted in breast cancer. Thirteen EGFR expressing breast cancer cell lines were analyzed for response to EGFR TKIs. Seven were found to be EGFR TKI resistant; while shRNA knockdown of EGFR determined that four of these cell lines retained the requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
151
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(169 citation statements)
references
References 59 publications
10
151
0
Order By: Relevance
“…Further examination of the localization of EGFR revealed that in both fibroblasts and myofibroblasts, EGFR was associated and co-localized with areas of high cholesterol content, otherwise known as cholesterol-rich microdomains or lipid rafts (48). These findings supported previous reports of EGFR being bound in lipid raft domains in other cell systems (49) and of lipid rafts as regulators of EGFR and other receptors (50,51,52). CD44 was found to co-localize with lipid raft domains after differentiation of fibroblasts to myofibroblasts, supporting the hypothesis that CD44 relocalization to lipid rafts containing EGFR was implicated in the differentiation pathway.…”
Section: Discussionsupporting
confidence: 86%
“…Further examination of the localization of EGFR revealed that in both fibroblasts and myofibroblasts, EGFR was associated and co-localized with areas of high cholesterol content, otherwise known as cholesterol-rich microdomains or lipid rafts (48). These findings supported previous reports of EGFR being bound in lipid raft domains in other cell systems (49) and of lipid rafts as regulators of EGFR and other receptors (50,51,52). CD44 was found to co-localize with lipid raft domains after differentiation of fibroblasts to myofibroblasts, supporting the hypothesis that CD44 relocalization to lipid rafts containing EGFR was implicated in the differentiation pathway.…”
Section: Discussionsupporting
confidence: 86%
“…Statins have been reported to inhibit the growth of JAK2-mutated cells by inhibiting lipid rafts (23) and inducing apoptosis by inhibiting Rac1 (15). Thus, lipid rafts act as a platform for collecting multiple stimulants, receptors, and signals to activate cancer progression (24). The mechanism of integration of EA to cholesterol raft should be elucidated in further examinations; however, our data suggests that lipid rafts may be promising targets for anticancer treatment.…”
Section: Discussionmentioning
confidence: 83%
“…In some EGFR-TKI-resistant breast cancers, Met and c-Src tyrosine kinases are overexpressed, hyperactivating EGFR even in the presence of the inhibitor (5). Furthermore, in EGFR-TKI-resistant breast cancer cell lines, EGFR is localized at lipid rafts even in the presence of the drug, leading to hyperactivation of the downstream Akt signaling (50). In the present study, we examined whether there were additional molecular modulations that confer EGFR-TKI resistance in breast cancer.…”
Section: Discussionmentioning
confidence: 97%